The Influence of Social Media on Language Evolution: A Sociolinguistic Perspective Study on English Language Students at the Faculty of Education, Al-Qusai'ah, Azzaytuna University - Mohammed Jamal Amhimmid (Aljameai, 2025)
Abstract:Social media transformed people's means of communication and altered the evolution of the English language in unprecedented manners. The rapid evolution of internet slang, emoticons, abbreviations, and meme language are testaments to the vitality of online communication and its impact on informal and formal language use. The study will employ Labov's sociolinguistic theory to analyze dramatic linguistic change such as mimetic linguistics. The study uses a mixed-methodologies strategy, integrating qualitative and quantitative methods, to investigate the contribution of social media towards the development of the English language. The study demonstrated that social media is a potent linguistic power that influences vocabulary, styles of communication, and even the utilization of formal language. But it encourages innovation and interaction.المستخلص:   غيّرت وسائل التواصل الاجتماعي أساليب تواصل الأفراد وأثرت على تطور اللغة الإنجليزية بطرق غير مسبوقة. يُعَد التطور السريع للمصطلحات العامية عبر الإنترنت، والرموز التعبيرية، والاختصارات، ولغة الميمات دليلًا على حيوية التواصل عبر الإنترنت وتأثيره على استخدام اللغة في السياقات الرسمية وغير الرسمية. ستعتمد هذه الدراسة على نظرية علم اللغة الاجتماعي لِلابوف لتحليل التغيرات اللغوية الجذرية، مثل علم اللغة الميمي. تستخدم الدراسة منهجية مختلطة تجمع بين الأساليب النوعية والكمية للتحقيق في إسهام وسائل التواصل الاجتماعي في تطور اللغة الإنجليزية. وأظهرت الدراسة أن وسائل التواصل الاجتماعي تُعد قوة لغوية مؤثرة تسهم في تشكيل المفردات وأساليب التواصل وحتى استخدام اللغة الرسمية، كما أنها تشجع على الابتكار والتفاعل.